Productive capacities, structural economic vulnerability and fiscal space volatility in developing countries - Sèna Kimm Gnangnon (KDI Journal of Economic Policy, 2023)
The current article has explored the effect of productive capacities (as defined by the United Nations Conference on Trade and Development) and of structural economic vulnerability (as defined by the United Nations) on fiscal space volatility in developing countries. It relies on the definition and measure of fiscal space proposed by Aizenman and Jinjarak (2010; 2011) and Aizenman et al. (2019). To compute the indicator of fiscal space and hence that of fiscal space volatility, fiscal space is considered as the ratio of outstanding public debt to the 'de facto tax base', the latter being the number of years of tax revenues needed for a country to repay its debt. Results based on a sample of 116 countries from 2000 to 2018 have revealed that the enhancement of productive capacities is associated with lower fiscal space volatility, while higher structural economic vulnerability heightens fiscal space volatility. On another note, highly vulnerable countries tend to experience a higher negative effect of productive capacities on fiscal space volatility than relatively less vulnerable countries.
Keywords: D24; O10; E60; 330; Productive capacities; Structural economic vulnerability; Fiscal space volatility